Augmented Reality Development for Creating Interactive Experiences in Tourism Places - Pranata, Caraka Aji; Filza, Muhammad Fairul; Tanudidjaja, Miquel Jan (Journal of Applied Informatics and Computing, 2025)
Technology, hardware and software are developing rapidly as time goes by. One of the results of this rapid technological development is Augmented Reality (AR) technology. Current tools in augmented reality (AR) were offered by Vuforia Software Development Kit (SDK). However, with the rapid development of Unity Engine, now we can integrated OpenCV in Unity Engine. This integration presents ideas for the development of AR technology. This study uses an approach that uses research and development (R&D) methodology. The model that will be used is the utilization of the ADDIE development framework. We encountered three main problems, problems faced are "How many stages of implementing AR with mediapipe in Unity Engine?", “How people satisfaction while using this product?” and " What is the maximum distance and time required to conduct the interaction process?". From the research conducted, we found that there are four important AR development stages that must be carried using Unity Engine and OpenCV. Next for RQ2 we got a level of approval from users of 86.53% or strongly agree with what we are doing. Then for the last RQ, we got the results for optimal hand detection distance is 3 meters, and the speed with the fastest value is 0.098s.